Aktualisasi Pendidikan Akhlak Pada Kitab Ayyuhal Walad Dalam Kehidupan Sehari-Hari - Bima Praditya, Alvathera; Ichsan, Yazida; Nailatsani, Fathinahaya; Syifa Miasari, Rahmalia (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2022)
Education understands the process of developing all aspects that exist in humans, including cognitive, affective, and psychomotor. Current educational developments that do not prioritize character education need to be re-integrated with transparent sources. The importance of character and moral education aims to achieve academic goals in harmony with human social life. Good moral education will produce individuals who can support themselves and their environment well and provide positive stimuli for the surrounding environment. Moral or behavior is a critical issue inherent in a person. Discussions related to morality and personality have been studied by several salaf and khalaf scholars. They compiled several unique books related to ethics, morals, and character that is genuinely for a Muslim. The book of Ayyuhal Walad written by Al-Ghazali, describes a commentary on ethics and morals. Through the literature study research method, the contents of the book of Ayyuhal Walad in the character education section can be peeled and analyzed. Humans are social creatures who cannot live alone. Good morals are needed in delivering humans to act and behave humanely towards other humans. The article entitled Actualization of Moral Education in the Ayyuhal Walad Book in Daily Life has several purposes. One of the most important is to explain how the concept of implementing moral education is contained in the book. The contents of the book of Ayyuhal Walad in the character education section can be peeled and analyzed. Humans are social creatures who cannot live alone. Good morals are needed in delivering humans to act and behave humanely towards their environment and other humans. The article entitled Actualization of Moral Education in the Ayyuhal Walad Book in Daily Life has several purposes. One of the most important is to explain how the concept of implementing moral education is contained in the book. The contents of the book of Ayyuhal Walad in the character education section can be peeled and analyzed. Humans are social creatures who cannot live alone. Good morals are needed in delivering humans to act and behave humanely towards their environment and other humans. The article entitled Actualization of Moral Education in the Ayyuhal Walad Book in Daily Life has several purposes. One of the most important is to explain how the concept of implementing moral education is contained in the book.